Primary Resistance to EGFR Tyrosine Kinase Inhibitors (TKIs): Contexts and Comparisons in EGFR-Mutated Lung Cancer - Keigo Kobayashi (MDPI AG, 2023)
The discovery of the efficacy of tyrosine kinase inhibitors (TKIs) in epidermal growth factor receptor (EGFR)-mutated non-small-cell lung cancer (NSCLC) patients has revolutionized lung cancer therapy. Although almost all responders acquire drug resistance within a few years, many studies have revealed several acquired-resistant mechanisms and developed therapeutic strategies countervailing them, most notably against the EGFR T790M gatekeeper mutation. However, little progress has been made in terms of elucidating the mechanisms of primary resistance. Primary resistance may be defined into two types of resistance, clinically representing patients that do not respond (non-responders) to EGFR-TKIs. The first group consists of approximately 10% of patients that are insensitive to EGFR-TKIs from the outset (intrinsic primary resistance), and 20-30% of the second group consists of patients that seem to clinically benefit at first, but experience early relapse within six months (late primary resistance). In this review, we first provide an overview of drug-induced lung cancer dynamics. We then delve into the mechanisms of primary resistance, with a primary focus on two specific subtypes of resistance. We suggest that "intrinsic primary resistance" is characterized by pre-existing somatic and genomic changes and cell of origins, while "late primary resistance" is correlated with the drug-tolerant persister state. Developing therapeutic strategies to overcome primary resistance is crucial to prolonging the duration of EGFR-TKI therapy. Ultimately, this will allow for an enhanced understanding of lung cancer's evolutional process, leading to the reversal of acquired resistance and the complete eradication of lung cancer.